A novel two-dimensional coupled lattice Boltzmann model for incompressible flow in application of turbulence Rayleigh–Taylor instability. (12th October 2017) - Wei, Yikun; Dou, Hua-Shu; Qian, Yuehong; Wang, Zhengdao
Highlights: A novel coupled lattice Boltzmann model is developed for two-dimensional incompressible Rayleigh–Taylor instability. A modified equilibrium distribution function is proposed in this paper. A mesoscopic discrete force is in the modified equilibrium distribution function. Excellent agreement is demonstrated between the present results and the other numerical method or analytical solution. The present model is an efficient numerical method for Rayleigh–Taylor instability. Abstract: A novel coupled lattice Boltzmann model is developed for two-dimensional incompressible Rayleigh–Taylor instability. a modified equilibrium distribution function (D2Q13)is proposed in this paper. The present model is stable and reliable up to temperature jumps between top and bottom walls of the order of 50 ϰ the averaged bulk temperature. The regimes of mixing Rayleigh–Taylor instability are discussed using a simple scaling and the scaling relations obtained are validated by the present model. It is demonstrated that excellent agreement between the present results and the other numerical method or analytical solution shows that the present model is an efficient numerical method for Rayleigh–Taylor instability.